EMPOWERING THE NEXT GENERATION: PRACTICAL DISASTER PREPAREDNESS TRAINING FOR ELEMENTARY STUDENTS - Prodyanatasari, Arshy; Diasandy, Deva Raka Satria; Azizah, Laila Nur; Izati, Lufia Elen Ayu; Hidayat, Abdullah Farikh (PENA DIMAS: Jurnal Pengabdian Masyarakat, 2025)
Disaster response training serves as both a preventive measure and an investment in community safety and resilience. By equipping students with knowledge and skills in disaster preparedness, this training fosters a generation capable of protecting themselves and minimizing risks and losses. Indonesia's high vulnerability to disasters, particularly in Kediri City, which is prone to floods and earthquakes, underscores the importance of such training. The primary goal is to prepare students to handle emergencies effectively. Using the Participatory Action Research method, students actively participate in disaster evacuation simulations. The training was conducted on May 21, 2024, targeting all students in grades I-VI at SDN YBPK Semampir, Kediri City. Pre-tests and post-tests were used to assess the training's effectiveness, showing significant knowledge improvement, with post-test scores consistently higher. Statistical analysis confirms this with a significant difference (p < 0.001). The training has proven successful at SD YBPK Semampir, enhancing students' disaster preparedness. To sustain this impact, it is recommended that the training be conducted regularly, involve parents, and develop more comprehensive modules. These steps can strengthen disaster awareness and preparedness in schools and the community. Further development of this initiative should include in-depth needs assessments and improved training modules.